Selected exercise and skeletal muscle characteristics of African distance runners - Weston, Adele Robyn (MRC/UCT RU for Exercise and Sport Medicine, 2017)
African runners dominate distance running both in South Africa and internationally. Therefore, the aim of this thesis was to compare selected exercise and skeletal muscle characteristics in well-trained African and Caucasian 10 km runners to determine if evidence exists of differences between these groups with respect to these physiological and biochemical characteristics. Furthermore, the relationship between exercise and skeletal muscle characteristics was investigated. Sedentary individuals from each population group were also studied to determine if differences existed in untrained skeletal muscle between groups. Maximal oxygen consumption and peak treadmill speed were measured using an incremental treadmill protocol whilst submaximal exercise characteristics were measured during a specifically designed protocol consisting of four sequential submaximal workloads relative to the peak treadmill speed of the individual. The final workload was maintained until fatigue with resistance to fatigue defined as total test time. Running economy was measured at a treadmill speed of 16.1 km/hr. Race pace characteristics were measured directly at race pace. Characteristics measured during exercise tests were oxygen uptake, minute ventilation, respiratory exchange ratio and heart rate whilst plasma lactate concentration was determined immediately after exercise. Skeletal muscle characteristics were determined by needle biopsy of the vastus lateralis muscle. Skeletal muscle enzymes citrate synthase, phosphofructokinase, 3-hydroxyacyl CoA dehydrogenase, hexokinase and carnitine palmityl transferase were assayed spectrophotometrically. Skeletal muscle buffering capacity was measured using by titration and fibre type proportions were analysed histochemically. Comparisons between groups were made with the Student's t-test for unpaired data whilst the relationships between variables were analysed using the Pearson's correlation coefficient. The first major finding was that when exercising at the same relative percentage of individual maximal treadmill velocity, African distance runners were able to exercise for longer than the Caucasians (1376±227 vs 1137±126 sec, p<0.01) with lower plasma lactate accumulation (4.8±3.2 vs 7.7±2.8 mmol/l,p<0.05). Time to fatigue was significantly related to a lower plasma lactate concentration (r=-0.63) and a lower respiratory exchange ratio (r=-0.53). The second major finding indicated that African runners were able to race 10 km at a higher percentage of their maximal oxygen uptake (93.5 vs 86.0%, p<0.005), whilst eliciting only a comparable plasma lactate concentration and respiratory exchange ratio. The third main finding was that the African runners were more economical than the Caucasian runners (p<0.05). The fourth main finding is that the African runners had a 50% greater activity of citrate synthase (p<0.005) and 3-hydroxyacyl CoA dehydrogenase (p<0.01) in the vastus lateralis than the Caucasians and this could not be explained by fibre type proportions, because the proportion of type I fibres was lower in the African runners (p<0.05). Citrate synthase activity, was related to the runners' ability to resist fatigue at high intensity relative to their individual peak treadmill velocity (r=0.70, p<0.05). A higher CS activity was related to a lower plasma lactate concentration and a lower RER. The sixth main finding of this thesis was that skeletal muscle buffering capacity of the Caucasian runners was higher than that of the African runners (p<0.05). A methodological study of buffering capacity in rats showed the buffering capacity was largely dependent upon fibre type and protein concentration, however these parameters could not explain the difference observed between the African and Caucasian runners. Furthermore, despite the differences in skeletal muscle characteristics observed between African and Caucasian runners in the current thesis, there was no evidence of these differences being inherently present in sedentary African and Caucasian individuals. In conclusion, the current series of studies do provide evidence of differences in selected exercise and skeletal muscle characteristics between African and Caucasian distance runners, with the African runners possessing exercise and skeletal muscle profiles that are considered to be more advantageous for endurance performance.